Antioxidant and Antigenotoxic Activities of the Brazilian Pine Araucaria angustifolia (Bert.) O. Kuntze - Márcia O. Souza; Cátia S. Branco; Juliane Sene; Rafaela DallAgnol; Fabiana Agostini; Sidnei Moura; Mirian Salvador (Antioxidants, 2014)
Polyphenols are natural products with recognized potential in drug discovery and development. We aimed to evaluate the polyphenolic profile of Araucaria angustifolia bracts, and their ability to scavenge reactive species. The antioxidant and antigenotoxic effects of A. angustifolia polyphenols in MRC5 human lung fibroblast cells were also explored. The total polyphenol extract of A. angustifolia was determined by the Folin–Ciocalteu reagent and the chemical composition was confirmed by HPLC. Reactive oxygen species’ scavenging ability was investigated by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and superoxide dismutase- and catalase-like activities. The protective effect of the extract in MRC5 cells was carried out by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide method and the determination of oxidative lipids, protein, and DNA (alkaline and enzymatic comet assay) damage. Total phenolic content of the A. angustifolia extract was 1586 ± 14.53 mg gallic acid equivalents/100 g of bracts. Catechin, epicatechin, quercetin, and apigenin were the major polyphenols. The extract was able to scavenge DPPH radicals and exhibited potent superoxide dismutase and catalase-like activities. Moreover, A. angustifolia extract significantly protected MRC5 cells against H2O2-induced mortality and oxidative damage to lipids, proteins, and DNA. Therefore, A. angustifolia has potential as a source of bioactive chemical compounds.